1997
DOI: 10.1097/00042560-199701010-00010
|View full text |Cite
|
Sign up to set email alerts
|

Rates of and Factors Associated with Self-reported Prior HIV Testing Among Adult Medical Patients in an Inner City Emergency Department in the Bronx, New York City

Abstract: We studied the rates of and factors associated with self-reported prior human immunodeficiency virus (HIV) testing in adult patients visiting an emergency department (ED) in the Bronx, New York City. A total of 1,744 consecutive noncritical adult medical emergency patients responded to a standardized interview administered by ED physicians. The interview included questions pertaining to demographic characteristics, prior HIV testing, and HIV risk behaviors. On multivariate analysis, female gender, younger age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 13 publications
5
15
0
Order By: Relevance
“…It is estimated that at least more than half of all HIV infections (almost 7,000 daily) worldwide occur among young people aged between 15 and 24 years 3 . The situation is especially serious in developing countries where young people form a significant proportion and where the HIV epidemic has been most severe 3 .…”
Section: By Omary Sukari Md5 2007/08mentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that at least more than half of all HIV infections (almost 7,000 daily) worldwide occur among young people aged between 15 and 24 years 3 . The situation is especially serious in developing countries where young people form a significant proportion and where the HIV epidemic has been most severe 3 .…”
Section: By Omary Sukari Md5 2007/08mentioning
confidence: 99%
“…The situation is especially serious in developing countries where young people form a significant proportion and where the HIV epidemic has been most severe 3 . With young people at the centre of the epidemic, it is important to understand the extent to which they are willing aBsTRacT:…”
Section: By Omary Sukari Md5 2007/08mentioning
confidence: 99%
“…Female gender, younger age, race, and being single are positively associated with HIV testing behavior (Bond et al 2005;Burchell et al 2003;Shuter et al 1997). Greater AIDS knowledge and higher education (Gage and Ali 2005;Stein and Nyamathi 2000), a history of an STD and injection drug use (Burchell et al 2003;Goodman and Berecochea 1994;Shuter et al 1997;Stolte et al 2003) were found to be significant predictors of having taken an HIV test. Higher perceived risk for HIV was found to be consistently associated with increased likelihood of having been tested for HIV (Downing et al 2001;Maman et al 2001;Stein and Nyamathi 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of individuals who have tested for HIV has remained relatively stable since the mid 1990's (CDC, 2003). There is evidence that many high-risk persons have never tested (Shuter et al, 1997;CDC, 1999;Fleming et al, 2002), or do not re-test after engaging in high-risk behaviors for HIV (Simon et al, 1996;Liebman et al, 1996). Improving our understanding of how individuals make the decision to get tested is essential to increase rates of HIV testing and re-testing among persons at HIV risk.…”
Section: Introductionmentioning
confidence: 99%